Review of International Accounting Information Systems - Beke, Jeno (Asian Accounting and Auditing Advancement, 2011)
This paper traces the benefits of international accounting information systems-their contribution to standardization and harmonization by purposing and tasking for business management. In this review, the goal is to describe and summarize how the accounting information system can help management decisions and influence the business environment on a global scale. The unified, standardized accounting information system will lead to new types of analysis and data, furthermore with the possible integration of new indicators from the business management practice of certain countries. The purpose of this study was the measure the differences between the national rules and the international methods by countries, then the value and analyze their effects on the business environments. The study showed that both business earnings and stock returns affect management turnover. Businesses with lower labor productivity compared to their industry peers have greater incentives to adopt an international accounting system. However, the results on turnover are sensitive to this change in variable specification. So the increase in the sensitivity of turnover to accounting performance postadoption is primarily driven by heightened turnover sensitivity to accounting losses. The empirical results could be the author’s suggestions for business management. JEL Classification Code: M40, M41, M48